Determinasi Sosial dalam Memilih Pasangan Hidup Melalui Perkawinan Nyentana pada Masyarakat Hindu di Bali - Sri Pratiwi, Ni Putu; Nurwati, Nunung; Sekarningrum, Bintarsih (Jayapangus Press, 2024)
Nyentana marriage has both positive and negative impacts on sentana rajeg. Although nyentana marriage in Bali supports gender equality, sentana rajeg faces significant challenges in implementing a matrilineal kinship pattern amidst patrilineal dominance, leading to difficulties in choosing a life partner. The aim of this study is to describe the current condition of nyentana marriage, analyze the forms of social determination experienced by sentana rajeg, and explore the social practices undertaken by sentana rajeg in seeking a life partner. This research employs a qualitative method with a descriptive-explanatory and descriptive-exploratory approach. Data collection techniques include in-depth interviews, observation, and document studies. Data analysis is conducted based on social practice theory. The study finds that the acceptance of nyentana marriage among the Balinese Hindu community is relatively slow due to the social stigma of